Lessons Learned and Not Yet Learned from a Multicountry Initiative on Women's Economic Empowerment - Johansson de Silva, Sara; Paci, Pierella; Posadas, Josefina (Washington, DC: World Bank, 2013)
The Results-Based Initiatives (RBI), launched in 2007, were a pioneering attempt to provide comprehensive, coherent, and rigorous evidence on effective interventions to foster the economic empowerment of women. The RBI comprised five small pilots with built-in impact evaluation designed to identify what works best in promoting better outcomes for women as entrepreneurs, wage earners or farmers, under different country contexts. The program was an innovative experiment in an important policy area. While there is a clear rationale for policy interventions to help remove constraints to women’s economic empowerment, knowledge of what interventions work best in different settings remains limited. When the RBI were conceived, rigorous evidence in this area was close to nonexistent because no systematic impact evaluations had been carried out in developing countries. However, the RBI fell short of meeting several of their ambitious objectives. This study highlights lessons from the RBI with respect to both the impact of the interventions and dos and don’ts in the design and implementation of pilots. Regarding the impact on economic opportunities, the interventions did not generally increase women’s earnings, with the exception of the Peru pilot. However, women who received training generally appreciated the access to new information and felt their skills and their involvement in business associations and networks had increased. However, it would be wrong to conclude that these interventions were not effective. The lack of robust positive impact may be due to the evaluations being conducted too soon to show fully the long-term effects of the interventions, or to problems in the design, implementation, or measurement of pilot outcomes. In particular, there was a clear need of an “early warning system” to synchronize the corrections in the interventions with the design of the impact evaluation. The RBI were overambitious regarding what could be achieved with a limited budget and a short time frame.